DIRECT DISTILLATION TECHNIQUE FOR ACCURATE CARBON DIOXIDE QUANTIFICATION IN WATER - Turner, Alexander William (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
High-pressure solvent extraction (HPSE) has gained prominence in various industries, including chemical, food, and pharmaceutical sectors, owing to its numerous advantages. In this study, we explore the application of HPSE, particularly using CO2 as the solvent, for the extraction of valuable compounds from marigold (Calendula officinalis L.), a plant with a wide range of applications in traditional medicine and modern formulations. Conventional extraction processes, such as steam distillation and solvent extraction, often entail additional separation steps and exhibit lower selectivity when compared to CO2-based HPSE. The unique characteristics of HPSE, including lower operating temperatures and reduced water content, contribute to the prevention of thermal degradation and hydrolysis of active compounds in the plant material. As a result, the extracts obtained through HPSE retain the integrity of active compounds and exhibit scents more akin to the original plant material. Marigold, a well-cultivated plant in Europe and America, serves both ornamental and medicinal purposes. Traditional medicine has long employed marigold flowers to treat a variety of conditions, including inflammatory disorders of internal organs, gastrointestinal ulcers, diuretic and diaphoretic convulsions. Additionally, marigold extracts find applications in diverse pharmaceutical preparations, particularly in ointments for dermatological conditions such as ulcers, eczema, burns, and hemorrhoids. Pharmacological studies of conventional marigold extracts, which include infusions, tinctures, and fluid extracts, have revealed that saponins, glycosides of sesquiterpenes, flavonoids, and triterpenes constitute the most vital constituents in these extracts. This research aims to elucidate the potential of HPSE, specifically CO2-based extraction, for preserving the integrity of marigold's bioactive compounds and enhancing the quality of the obtained extracts. The study will focus on the extraction process, the preservation of active compounds, and the sensory properties of marigold extracts. Moreover, we anticipate that this research will contribute to the development of more effective and sustainable extraction methods in the chemical, food, and pharmaceutical sectors